2017
DOI: 10.1186/s12913-017-2630-4
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of patient advisors on healthcare outcomes: a systematic review

Abstract: BackgroundPatient advisory councils are a way for healthcare organizations to promote patient engagement. Despite mandates to implement patient advisory councils through programs like the Patient-Centered Medical Home (PCMH), there is a paucity of data measuring the impact of patients functioning in advisory roles. Our objective is to investigate whether patient engagement in patient advisory councils is linked to improvements in clinical quality, patient safety or patient satisfaction.MethodsWe searched PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 38 publications
3
89
0
3
Order By: Relevance
“…PFACs are groups of patients, family members and family caregivers who serve as advisors in diverse health‐care settings, from individual clinics and hospitals to entire health systems. PFACs can be seen as part of a broader global movement over the past two decades towards patient and public involvement in health‐care planning …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PFACs are groups of patients, family members and family caregivers who serve as advisors in diverse health‐care settings, from individual clinics and hospitals to entire health systems. PFACs can be seen as part of a broader global movement over the past two decades towards patient and public involvement in health‐care planning …”
Section: Introductionmentioning
confidence: 99%
“…However, PFACs’ potential may be underutilized. While case studies suggest how PFACs could improve the safety and quality of patient care, systematic and structured reviews have repeatedly demonstrated a lack of rigorous evaluation and evidence of such impact . Much work remains to ensure PFACs can further patient‐ and family‐centred change in diverse health‐care settings …”
Section: Introductionmentioning
confidence: 99%
“…Future work is necessary to establish whether community engagement is primarily an ethical consideration to ensure public health interventions are equitable, versus a means to also ensure interventions are more accessible, user friendly, and effective. There is a small but growing evidence base that patient or consumer involvement can help elicit more patient-centered priorities, educational materials, and communication strategies for general primary care 4852 ; these assessment methodologies could be adapted to future family planning initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 systematic review found few robust studies evaluating the impact of patient advisers on health out comes but noted case studies that described improvements in appointment access, patient safety and patient satisfaction. 2 A more recent systematic review found that patient engagement resulted in enhanced care or service delivery, particularly if an organization used methods of codesign. 3 Experiencebased codesign begins with an indepth exploration of the experiences and emotions of patients and then brings patients and staff together to identify and implement improvements in service.…”
mentioning
confidence: 99%
“…In some cases, patients who are engaged have improved outcomes themselves. 2 Even though engaging patients to improve services is benefi cial, it is also new for many clinicians and managers. Figure 1 offers suggestions for getting started by listing a range of meth ods that require varying levels of resources from providers and patients.…”
mentioning
confidence: 99%